EBF1, PAX5, and MYC: regulation on B cell development and association with hematologic neoplasms - Li, Li; Zhang, Daiquan; Cao, Xinmei (Frontiers in Immunology, 2024)
During lymphocyte development, a diverse repertoire of lymphocyte antigen receptors is produced to battle against pathogens, which is the basis of adaptive immunity. The diversity of the lymphocyte antigen receptors arises primarily from recombination-activated gene (RAG) protein-mediated V(D)J rearrangement in early lymphocytes. Furthermore, transcription factors (TFs), such as early B cell factor1 (EBF1), paired box gene 5 (PAX5), and proto-oncogene myelocytomatosis oncogene (MYC), play critical roles in regulating recombination and maintaining normal B cell development. Therefore, the aberrant expression of these TFs may lead to hematologic neoplasms.